AVALIAÇÃO ESPAÇO-TEMPORAL DE CRIADOUROS DE Aedes aegypti NA CIDADE DE CAMPO GRANDE, MS, BRASIL, ENTRE 2022 E 2023 - MARIANA MAYUMI ZANONI (2025)
Aedes aegypti (Diptera: Culicidae) is the primary vector of the etiological agents of dengue, Zika, chikungunya, and yellow fever, arboviruses of great public health relevance. With a holometabolous life cycle and a high adaptive capacity, vector control focuses on eliminating breeding sites. According to the Rapid Survey of Aedes aegypti Indices (LIRAa), breeding sites are water-holding containers conducive to larval development, classified into five distinct groups A (water tanks), B (movable containers), C (fix containers), D (removable containers), and E (natural containers). This study aimed to assess the occurrence of different types of breeding sites in Campo Grande, Mato Grosso do Sul, between 2022 and 2023. Specifically, it sought to analyze the influence of overcrowding and illiteracy on the distribution of these breeding sites, as well as to identify potential changes in their proportions over time. Data were obtained from the larval surveillance program of the Vector-Borne Endemic Disease Control Coordination (CCEV) and socioeconomic information from the Brazilian Institute of Geography and Statistics (IBGE). Analyses considered spatiotemporal variations in breeding site prevalence using an Additive Multilevel Multinomial Statistical Model with a Bayesian approach. Using water tanks as a reference, waste and mobile containers were the most significant breeding sites for mosquito proliferation, while natural sites had a lower impact. In overcrowded areas, mobile containers became more prominent, whereas water tanks decreased in importance. Fixed containers, waste, and natural breeding sites were not influenced by population density. In regions with higher illiteracy rates, mobile and fixed containers, as well as waste, decreased, whereas water storage breeding sites increased. These findings are essential for guiding entomological control strategies, contributing to the reduction of arbovirus incidence, particularly dengue, in Campo Grande, MS. Keywords: Arboviruses. Control measures. Entomological indicator. LIRAa.